Implementation of the Role of PAK Teachers in Developing the Character of Class XI Students of Medan Adventist Private High School - Nani Sri Rezeki; Harapan Simanjuntak (Journal of Golden Generation Multidisciplinary, 2025)
This research aims to determine the role of PAK teachers in shaping the character of class XI students at Medan Adventist Private High School in the 2022/2023 academic year. This type of research is descriptive correlational. The population in this study is the entire class XI of Medan Adventist Private High School as many as 30 people because the population is small, namely only 30 people, the entire population becomes the research sample, namely 30 people with sampling techniques. The data collection instrument for variable X is a questionnaire consisting of 20 items. With 4 options that were first tested to determine the validity and reliability while the instrument for variable Y Documentation is in the form of a list of student grades (DKN) at the school. The results of the analysis requirements for the normality test of the Role of PAK Teachers' data are distributed normally with the calculation results obtained as X2 count . < X 2 table (22.33 < 43.77) and the PAK learning outcomes are normally distributed with the calculation results obtained being X 2 count < X 2 table (18.85 < 43.77). The results of the linearity test of the data on the Role of PAK Teachers in Character Formation are linear with the equation Y = 22.77 + 1.22x, which is linear. The results of the correlation test obtained r count of 0.453 consulted with the critical price r at a significance level of 5% with the number of respondents being 30 people, the r table was obtained of 0.361, because the calculated r > r table (0.453 > 0.361) this shows that there is an influence of the Role of PAK Teachers in Character Formation of Class XI students of Medan Adventist Private High School in the 2022/2023 academic year. Furthermore, to test the significance of the correlation, a statistical test formula (t-test) was used, obtaining a calculated t of 3.41. This price was then consulted with the t table at a 95% significance level of 1.69, because the calculated t > bold t (3.41.169 α=0.05 with dk = n-2 (30-2=28) the t table is 1.69 because the calculated t > t table (3.41>1.69) this shows that there is a significant influence of the Role of PAK Teachers in the Formation of Character of Class XI Students of Medan Adventist Private High School in the 2022/2023 Academic Year. Thus, the research hypothesis is accepted as true.